A TPU modified resin foam material and molding method thereof
Through multi-blend and step-by-step extrusion technology, the aging problem of polyurethane foam materials in high temperature environments is solved, and the temperature resistance performance of the material is improved and comprehensive performance optimization is achieved.
Patent Information
- Application Number
- CN202211248870.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-10-12
AI Technical Summary
Existing polyurethane foam materials are prone to aging in high temperature environments, resulting in degradation or failure of thermal insulation performance, and their temperature resistance needs to be improved.
Thermoplastic polyurethane (TPU) foaming material is modified by a multi-blending method, and the material is prepared by step-by-step extrusion method, and EVA material is used as a carrier to wrap the foaming agent and crosslinking agent during the molding process to improve the temperature resistance of the material.
The prepared TPU modified foaming material has good temperature resistance, elasticity and comprehensive performance, and is suitable for daily necessities, sports goods, toys, decorative materials and thermal insulation fields.
Smart Images

Figure CN115584117B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, in particular to a TPU modified resin foaming material and a molding method thereof. Background Art
[0002] TPU is a linear polymer material generated by the reaction of diisocyanate, macromolecular polyol and chain extender. It is a thermoplastic polyurethane elastomer. It is a polymer material between rubber and plastic, and it is also a "new" environmentally friendly material. It has a wide range of uses, involving automobiles, electronics, construction, medical and other fields. Advantages: TPU has excellent mechanical strength, wear resistance, oil resistance and flexibility resistance, especially wear resistance; temperature resistance: -30-120℃. Disadvantages: poor heat resistance, hot water resistance and compression resistance, the appearance is easy to turn yellow, it is easy to stick to the mold, the processing technology requires precision, and the processing cost is high. Existing polyurethane plastic foam materials are usually used in sound insulation, vibration reduction and heat insulation components of household appliances such as water heaters, air conditioners and wall-mounted boilers. When the long-term use environment temperature reaches 80℃, the polyurethane foam material will show aging phenomena such as hardening, brittleness, cell shrinkage, cracking, etc., resulting in a decrease in the heat insulation and sound insulation performance of the material or even failure. Therefore, it is necessary to modify the temperature resistance of polyurethane foam materials. The present application mainly aims at improving the temperature resistance of polyurethane foam material.
[0003] The existing patent 103408922B "A thermoplastic polyurethane elastomer foam material and its preparation method" conducts mixing-molding foaming on thermoplastic polyurethane materials to obtain foam materials with certain comprehensive properties. However, judging from the material components used and the tested performance, the temperature resistance of the foam material is not particularly good. Although the Vicat softening point reaches up to 130°C, the heat deformation temperature will be lower and cannot meet the requirements of long-term high temperature resistance (such as 100°C). This application modifies the thermoplastic polyurethane (TPU) foam material by a multi-component blending method and prepares the material by a step-by-step extrusion method, which is more suitable for mass production and has high efficiency, and the temperature resistance of TPU is improved. Summary of the invention
[0004] In view of the above problems, the present invention discloses a TPU modified resin foam material and a molding method thereof.
[0005] The specific technical solutions are as follows:
[0006] A TPU modified resin foam material, comprising the following components in parts by weight:
[0007]
[0008] Preferably, the masterbatch is prepared from a foaming agent, a cross-linking agent dicumyl peroxide and an EVA material in a weight ratio of 10:1:14; they are mixed in a high-speed mixer, and blended and granulated using a twin-screw extruder, with EVA as a carrier to encapsulate the foaming agent and the cross-linking agent dicumyl peroxide.
[0009] Preferably, the filler is mica powder, quartz powder or kaolin.
[0010] Preferably, PBT is polybutylene terephthalate.
[0011] Preferably, the EVA material is ethylene-vinyl acetate copolymer.
[0012] A method for forming a TPU modified resin foam material comprises the following steps:
[0013] Step (1): Prepare the above materials according to the number of portions;
[0014] Step (2): mixing TPU, long-chain branched polypropylene, PBT, filler and antioxidant 1010 according to a weight ratio, and extruding and blending them using a co-rotating parallel twin-screw extruder to obtain a mixed material;
[0015] Step (3): Mix the masterbatch prepared from the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material with the mixed material using a high-speed mixer; then use a co-rotating parallel twin-screw extruder to perform blending and extrusion foaming to obtain a TPU modified foaming material.
[0016] Preferably, the high-speed mixer is a RH-10 high-speed mixer produced by Liaoning Fuxin Light Industry Electromechanical Equipment Factory, with a maximum speed of 8000 rpm;
[0017] Preferably, the co-rotating parallel twin-screw extruder used is the SHJ-35 co-rotating parallel twin-screw extruder produced by Nanjing Guangda Rubber and Plastic Machinery Factory.
[0018] The beneficial effects of the present invention are:
[0019] The present invention firstly prepares the master batch material of the foaming agent and the cross-linking agent dicumyl peroxide at low temperature and cannot be directly blended in TPU or other materials, because these materials have high melting points, which will cause the foaming agent and the cross-linking agent dicumyl peroxide to decompose and fail to prepare the sample. The EVA material selects a grade with a lower melting point to ensure that the foaming agent and the cross-linking agent dicumyl peroxide do not decompose. Moreover, the EVA material has a certain polarity and has a certain compatibility with TPU, long-chain branched polypropylene and PBT, which is beneficial to improving the performance of the product.
[0020] Thermoplastic elastomer TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed and extruded into granules. The extrusion temperature ensures that the material is melted, and there is no foaming agent and cross-linking agent in the mixed material. This lays a good foundation for the subsequent mixed foaming molding of masterbatch and mixed material.
[0021] Finally, the masterbatch and the material are blended and foamed by extrusion blending to obtain a TPU modified foaming material.
[0022] TPU is a highly polar material, while long-chain branched polypropylene is also polar. PBT material has certain heat resistance and is also a polar material. The masterbatch matrix EVA also has certain polarity, so the four materials have good compatibility. Long-chain branched polypropylene has high melt strength, which is conducive to the foaming of the blended material, and its temperature resistance is higher than that of the corresponding polypropylene, which is conducive to improving the temperature resistance of TPU materials. The four materials are mixed, combining their respective advantages, such as the mechanical strength, wear resistance, and oil resistance of TPU, the high melt strength of long-chain branched polypropylene, good foaming performance, and good temperature resistance, PBT has good heat resistance and processing performance, and EVA material has good foaming performance. In addition, the filling of inorganic materials has made a certain contribution to improving the temperature resistance and mechanical properties of the blended materials.
[0023] By adopting the above measures, a TPU, long-chain branched polypropylene, PBT, and EVA material blended modified foam material with uniform pores and low density is prepared. This foam material has good temperature resistance, elasticity and comprehensive performance, excellent mechanical properties, cold resistance, oil resistance, aging resistance, water resistance, and weather resistance, and can be used in daily necessities, sports goods, toys, decorative materials, thermal insulation and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an electron microscope image of the TPU modified foam material obtained in Example 1 of the present invention;
[0025] Figure 2 This is an electron microscope image of the TPU modified foam material obtained in Example 2 of the present invention;
[0026] Figure 3 This is an electron microscope image of the TPU modified foam material obtained in Example 3 of the present invention;
[0027] Figure 4 This is an electron microscope image of the TPU modified foam material obtained in Comparative Example 1 of the present invention;
[0028] Figure 5 This is an electron microscope image of the TPU modified foam material obtained in Comparative Example 2 of the present invention;
[0029] Figure 6 This is an electron microscope image of the TPU modified foam material obtained in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the technical solution of the present invention clearer and more specific, the present invention is further described below in conjunction with embodiments. Any equivalent replacement of the technical features of the technical solution of the present invention and any solution derived by conventional reasoning shall fall within the protection scope of the present invention.
[0031] The masterbatch is prepared from a foaming agent, a cross-linking agent dicumyl peroxide and EVA material, with a weight ratio of 10:1:14; the masterbatch is mixed in a high-speed mixer, and a twin-screw extruder is used for co-blending and granulation, and EVA is used as a carrier to encapsulate the foaming agent and the cross-linking agent dicumyl peroxide.
[0032] The temperatures of each zone of the twin-screw extruder for masterbatch manufacturing are as follows:
[0033] Zone 1 Zone 2 Zone 3 District 4 District 5 50℃ 55℃ 70℃ 80℃ 80℃ District 6 District 7 District 8 District 9 Machine head 80℃ 80℃ 80℃ 90℃ 85℃
[0034] A method for forming a TPU modified resin foam material comprises the following steps:
[0035] Step (1): Prepare the above materials according to the number of portions;
[0036] Step (2): mixing TPU, long-chain branched polypropylene, PBT, filler and antioxidant 1010 according to a weight ratio, and extruding and blending them using a co-rotating parallel twin-screw extruder to obtain a mixed material;
[0037] The temperature of each zone of the twin-screw extruder in step (2) is as follows:
[0038] Zone 1 Zone 2 Zone 3 District 4 District 5 150℃ 165℃ 180℃ 190℃ 200℃ District 6 District 7 District 8 District 9 Machine head 200℃ 210℃ 210℃ 210℃ 205℃
[0039] Step (3): Mix the masterbatch prepared from the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material with the mixed material using a high-speed mixer; then use a co-rotating parallel twin-screw extruder to perform blending and extrusion foaming to obtain a TPU modified foaming material.
[0040] The temperature of each zone of the twin-screw extruder in step (3) is as follows:
[0041] Zone 1 Zone 2 Zone 3 District 4 District 5 130℃ 140℃ 155℃ 165℃ 180℃ District 6 District 7 District 8 District 9 Machine head 190℃ 200℃ 205℃ 205℃ 200℃
[0042] Preferably, the high-speed mixer is a RH-10 high-speed mixer produced by Liaoning Fuxin Light Industry Electromechanical Equipment Factory, with a maximum speed of 8000 rpm;
[0043] Preferably, the co-rotating parallel twin-screw extruder used is the SHJ-35 co-rotating parallel twin-screw extruder produced by Nanjing Guangda Rubber and Plastic Machinery Factory.
[0044] Embodiment 1:
[0045] The foaming formula is:
[0046] 7.5 parts of EVA masterbatch, 54.2 parts of TPU, 19 parts of long-chain branched polypropylene, 14 parts of PBT, 6 parts of quartz powder (600 mesh), and 0.3 parts of antioxidant 1010.
[0047] The quartz powder was first surface treated with 1% coupling agent KH550.
[0048] The brand or model of the material is:
[0049] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0050] step:
[0051] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0052] In the second step, the masterbatch is prepared from foaming agent, cross-linking agent dicumyl peroxide and EVA material:
[0053] Step (1) First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio of (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0054] Step (2) TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0055] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0056] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0057] The foaming material was taken out and the foam density was measured to be 0.62 g / cm 3 , tensile strength is 0.41MPa, elongation at break is 80%, heat deformation temperature is 115℃, resilience is 55%, and the average cell diameter is about 0.41mm.
[0058] Embodiment 2:
[0059] The foaming formula is:
[0060] 7.5 parts of EVA masterbatch, 56.2 parts of TPU, 19 parts of long-chain branched polypropylene, 14 parts of PBT, 6 parts of quartz powder (600 mesh), and 0.3 parts of antioxidant 1010.
[0061] The quartz powder was first surface treated with 1% coupling agent KH550.
[0062] The brand or model of the material is:
[0063] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Crosslinking agent diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0064] step:
[0065] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0066] In the second step, the masterbatch is prepared from foaming agent, cross-linking agent dicumyl peroxide and EVA material:
[0067] Step (1) First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio of (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0068] Step (2) Thermoplastic elastomer TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0069] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0070] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0071] The foaming material was taken out and the foam density was measured to be 0.54 g / cm 3 , tensile strength is 0.52MPa, elongation at break is 80%, thermal deformation temperature is 103℃, resilience is 62%, and the average cell diameter is about 0.38mm.
[0072] Embodiment 3:
[0073] The foaming formula is:
[0074] 7.5 parts of EVA masterbatch, 56.2 parts of TPU, 14 parts of long-chain branched polypropylene, 14 parts of PBT, 3 parts of kaolin (1250 mesh), and 0.3 parts of antioxidant 1010.
[0075] Kaolin was first surface treated with 1% coupling agent KH550.
[0076] The brand or model of the material is:
[0077] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Crosslinking agent diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0078] step:
[0079] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0080] In the second step, the masterbatch is prepared from foaming agent, cross-linking agent dicumyl peroxide and EVA material:
[0081] Step (1): First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0082] Step (2) TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0083] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0084] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0085] The foaming material was taken out and the foam density was measured to be 0.46 g / cm 3 , tensile strength is 1.5MPa, elongation at break is 113%. Heat deformation temperature is 101.5℃. Rebound elasticity is 63%. The average cell diameter is about 0.3mm.
[0086] Comparative Example 1:
[0087] The foaming formula is:
[0088] 7.5 parts of EVA masterbatch, 50.2 parts of TPU, 19 parts of long-chain branched polypropylene, 14 parts of PBT, 9 parts of quartz powder (600 mesh), and 0.3 parts of antioxidant 1010.
[0089] The quartz powder was first surface treated with 1% coupling agent KH550.
[0090] The brand or model of the material is:
[0091] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Crosslinking agent diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0092] step:
[0093] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0094] In the second step, the masterbatch is prepared from foaming agent, cross-linking agent dicumyl peroxide and EVA material:
[0095] Step (1): First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0096] Step (2) TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0097] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0098] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0099] The foaming material was taken out and the foam density was measured to be 0.63 g / cm 3 , tensile strength is 0.63MPa, elongation at break is 100%, thermal deformation temperature is 101℃, resilience is 56%, and the average cell diameter is about 0.43mm.
[0100] This comparative example shows that a high amount of quartz powder is not conducive to improving the temperature resistance of the blended material.
[0101] Comparative Example 2:
[0102] The foaming formula is:
[0103] 7.5 parts of EVA masterbatch, 53.2 parts of TPU, 19 parts of long-chain branched polypropylene, 14 parts of PBT, 6 parts of kaolin (1250 mesh), and 0.3 parts of antioxidant 1010.
[0104] Kaolin was first surface treated with 1% coupling agent KH550.
[0105] The brand or model of the material is:
[0106] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Crosslinking agent diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0107] step:
[0108] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0109] In the second step, the masterbatch is prepared from a foaming agent, a cross-linking agent, dicumyl peroxide, and EVA material;
[0110] Step (1): First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0111] Step (2): TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0112] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0113] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0114] The foaming material was taken out and the foam density was measured to be 0.52 g / cm 3 , tensile strength is 0.75MPa, elongation at break is 53%. Heat deformation temperature is 90℃. Rebound elasticity is 60%. The average cell diameter is about 0.53mm.
[0115] This comparative example shows that a high amount of kaolin is not conducive to improving the temperature resistance of the blended material.
[0116] Comparative Example 3:
[0117] The foaming formula is:
[0118] 7.5 parts of EVA masterbatch, 50.2 parts of TPU, 19 parts of long-chain branched polypropylene, 14 parts of PBT, 9 parts of kaolin (1250 mesh), and 0.3 parts of antioxidant 1010.
[0119] Kaolin was first surface treated with 1% coupling agent KH550.
[0120] The brand or model of the material is:
[0121] TPU (brand name U-285AL), Kunzhong Co., Ltd. PBT, brand name 2024G00, Changchun Chemical (Zhangzhou) Co., Ltd. Foaming grade EVA brand name 1315, Hanwha, South Korea. Crosslinking agent diisopropylbenzene peroxide, industrial grade. Microsphere foaming agent, model ML2000, Jinshitou Plastic Raw Materials Co., Ltd. Antioxidant 1010, industrial grade. Quartz, 600 mesh, Xinlei Mineral Powder Processing Plant, Xingtang County, Hebei Province. Long-chain branched polypropylene can be prepared by melt grafting method, reference [Sun Ke, Cao Shenzhao, Yang Qi, et al. Study on long-chain branched polypropylene compatibilized polypropylene blends. China Plastics, 2014, 28(5): 27-31].
[0122] step:
[0123] Step 1: Preparation of experimental raw materials: prepare the raw materials according to the above requirements.
[0124] In the second step, the masterbatch is prepared from a foaming agent, a cross-linking agent, dicumyl peroxide, and EVA material;
[0125] Step (1): First, the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material are mixed in a high-speed mixer according to a weight ratio (10:1:14), and then blended and granulated in a twin-screw extruder, so that EVA is used as a carrier to wrap the foaming agent and the cross-linking agent diisopropylbenzene peroxide. The blending temperature in this step is low. EVA uses a low melting point grade 1315 with a melting point of 90°C to ensure that the foaming agent and the cross-linking agent diisopropylbenzene peroxide do not decompose.
[0126] Step (2): TPU, long-chain branched polypropylene, PBT, filler material, and antioxidant 1010 are mixed according to a ratio, and then extruded and blended in a twin-screw extruder to prepare a blended material. Antioxidant 1010 is used in this blending step.
[0127] Step (3) The master batch material obtained in step (1) and the blended material obtained in step (2) are first mixed in a high-speed mixer, and then blended, extruded and foamed in a twin-screw extruder to obtain a TPU modified foamed material.
[0128] Within this temperature range, the material softens and melts, the microsphere foaming agent in the masterbatch is heated, and the generated bubbles expand in the resin matrix. At the same time, the cross-linking agent diisopropylbenzene peroxide decomposes, and the resin matrix is partially cross-linked, which improves the melt strength, which is conducive to the matching of foaming and cross-linking.
[0129] The foaming material was taken out and the foam density was measured to be 0.61 g / cm 3 , tensile strength is 1.2MPa, elongation at break is 25%. Heat deformation temperature is 87℃. Resilience is 55%. The average cell diameter is about 0.23mm.
[0130] This comparative example shows that a high amount of kaolin is not conducive to improving the temperature resistance of the blended material.
[0131] The experimental data are as follows:
[0132]
[0133] The foaming material provided by the present invention is first prepared by an extrusion method, and the master batch containing a foaming agent and a cross-linking agent diisopropylbenzene peroxide is prepared with an EVA material as the matrix. Then, the thermoplastic elastomer TPU, long-chain branched polypropylene, PBT, a filling material, and an antioxidant 1010 are mixed and extruded and granulated by an extrusion method to prepare a premixed material. Then, the master batch and the premixed material are extruded by an extruder according to a proportion to prepare a TPU modified foaming material. The selected EVA matrix has a low melting point, which ensures that the foaming agent and the cross-linking agent diisopropylbenzene peroxide are not decomposed, and the EVA material has polarity and good compatibility with premixed materials such as TPU. Long-chain branched polypropylene is a resin with higher melt strength, better melt elasticity, and microgel content. Compared with cross-linked polypropylene, it has a low gel content, good processability, and can be recycled. PBT is a milky white translucent to opaque, semi-crystalline thermoplastic polyester with high heat resistance. In the present invention, TPU is mainly blended with long-chain branched polypropylene and PBT, and a certain amount of filling materials such as mica, kaolin, quartz powder, etc. are added to improve the performance of the material, and EVA masterbatch containing a foaming agent and a cross-linking agent is added to prepare a TPU modified foaming material.
[0134] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A TPU modified resin foam material, characterized by comprising the following components in parts by weight: TPU 50-70 parts; 10-30 parts of long chain branched polypropylene; PBT 10-30 parts; 1 to 3 parts of filler; Masterbatch 6-9 parts; Antioxidant 1010 0.3-0.6 parts; The masterbatch is prepared from a foaming agent, a cross-linking agent dicumyl peroxide and an EVA material, and the weight ratio thereof is 10:1:14; the masterbatch is mixed and prepared in a high-speed mixer, and a twin-screw extruder is used for co-blending and granulation, and EVA is used as a carrier to encapsulate the foaming agent and the cross-linking agent dicumyl peroxide; PBT is polybutylene terephthalate; The filler is mica powder, quartz powder or kaolin; EVA material is ethylene-vinyl acetate copolymer.
2. A method for forming the TPU modified resin foam material according to claim 1, characterized in that: The following steps are involved: Step (1): Prepare the above materials according to the number of portions; Step (2): mixing TPU, long-chain branched polypropylene, PBT, filler and antioxidant 1010 according to a weight ratio, and extruding and blending them using a co-rotating parallel twin-screw extruder to obtain a mixed material; Step (3): Mix the masterbatch prepared from the foaming agent, the cross-linking agent diisopropylbenzene peroxide and the EVA material with the mixed material using a high-speed mixer; then use a co-rotating parallel twin-screw extruder to perform blending and extrusion foaming to obtain a TPU modified foaming material.
Citation Information
Patent Citations
Thermoplastic polyurethane elastomer foam material and preparation method thereof
CN103408922B
Modified TPU (thermoplastic polyurethane) composite material for vehicle-mounted charging spring wires for electrical vehicles and preparation method thereof
CN104130567A
Light-weighted polyurethane foam material with high physical properties and preparation method of light-weighted polyurethane foam material
CN105273394A
Thermoplastic elastomers having improved set foams made therefrom
US6433090B1